The Effect of Uncertainty and Information Asymmetry on the Structure of Compensation Contracts: A Test of Competing Models - Umanath, Narayan S.; Ray, Manash R.; Campbell, Terry L. (Management Science, 1996)
This research note reports results of a laboratory experiment conducted as a follow-up investigation of an earlier study by Umanath, Ray and Campbell (Umanath, N. S., M. R. Ray, T. L. Campbell. 1993. The impact of perceived environmental uncertainty and perceived agent effectiveness on the composition of compensation contracts. Management Sci. (January) 32–45.). Here, we focus on a specific unexpected result of Umanath et al. who found evidence contradicting the theoretical prediction with respect to the impact of environmental uncertainty on the composition of compensation contracts. Umanath et al., in retrospect, offered an explanation for their unexpected finding based on an alternative theory under the same agency framework. Our results not only ratify the alternative explanation offered by Umanath et al., but also identify information symmetry/asymmetry as the contingent factor capable of reconciling the apparently contradicting predictions of the two agency-based theories used in this research.